2017
DOI: 10.18768/ijaedu.370407
|View full text |Cite
|
Sign up to set email alerts
|

The Exercise Group Technique on Academic Hardiness in Senior High School Students

Abstract: Academic stress related Hardiness (Benishek & Lopez, 2007). Academic hardiness provide positive framework for students to react toward academic challenges. Academic hardiness is the individual state of resilience toward academic failure: Individual who have academic hardiness display a willingness to engage in academic challenges, commit to follow all academic activities, and have control over academic performance for maximum results (Kobasa, Maddi, & Kahn, 1982).The purpose of this study is to determine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…(2017) in a study, titled as the effect of group hardiness training to high school students, showed a higher level of hardiness as a result of the intervention. [ 16 ] Zabihi et al . reported the positive effect of hardiness education on increased learning of self-regulation in the students.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) in a study, titled as the effect of group hardiness training to high school students, showed a higher level of hardiness as a result of the intervention. [ 16 ] Zabihi et al . reported the positive effect of hardiness education on increased learning of self-regulation in the students.…”
Section: Discussionmentioning
confidence: 99%
“…Esichaikul ,V.et al,2016,345, (Azevedo, R.;et al,2011,123 ( Bourekkache, et al, 2016,142 ) . ‫دي‬ ‫د‬ ‫ن‬ ‫ار‬ ‫و‬ ‫دة‬ ‫د‬ ‫اس‬ ‫ر‬ ‫و‬ ‫اتوال‬ ‫وبر‬ (Pratiwi ,2019;Mawarni, 2017) ‫وزمبتم‬ ‫رمو‬ ‫اسة‬ ‫ر‬ ‫و‬ (Clough, Earl, & Sewell, 2002) : ‫دة‬ ‫البدني‬ ‫دات‬ ‫الحرر‬ ‫و‬ ‫دة‬ ‫السعرفي‬ ‫دان‬ ‫السك‬ ‫ديل‬ ‫ب‬ ‫دوم‬ ‫مجسع‬ ‫ددما‬ ‫عش‬ ‫دل‬ ‫ز‬ ‫أ‬ ‫الخب‬ ‫يتعمم‬ (Hsu, 2011).…”
unclassified